2020
DOI: 10.1016/j.molliq.2020.113022
|View full text |Cite
|
Sign up to set email alerts
|

Drug carrier systems made from self-assembled glyco-nanoparticles of maltoheptaose-b-polyisoprene enhanced the distribution and activity of curcumin against cancer cells

Abstract: Controlled self-assembly of polymeric systems behave according to their composition and physicalchemical properties. Inclusion of a guest molecule may influence interactions and response to the media and to other surfaces and bodies, for example, cells. Hence, loading the polymeric system with curcumin (CUR), a natural and anticancer drug, confer interesting features to the carrier material.Micelle formation was achieved, in aqueous solution of carbohydrate-based block copolymer consisting in maltoheptaose-blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Therefore, refrigeration conditions were required. It has been reported that polyisoprenes show high stability in the presence of other polymers, and according to the composition of the latex, it has been identified proteins and carbohydrates that can act as adjuvants to complement their properties 15 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, refrigeration conditions were required. It has been reported that polyisoprenes show high stability in the presence of other polymers, and according to the composition of the latex, it has been identified proteins and carbohydrates that can act as adjuvants to complement their properties 15 …”
Section: Resultsmentioning
confidence: 99%